Spatial Spillover Effects in Food Security: A Spatial Lag Fixed Effects Model for Regencies and Cities in West Sumatra (2019–2023) - Tanjung, Fadhel Imam Haichal; Tanur, Erwin (Proceedings of The International Conference on Data Science and Official Statistics, 2025)
Food security is a key pillar of national development, reflecting a region’s ability to sustain food availability, accessibility, utilization, and stability. The Food Security Index (FSI) serves as a crucial measure of this capability. Based on 2023 data, West Sumatra Province achieved the highest FSI score on the island of Sumatra. This study analyzes food security in 19 regencies and cities of West Sumatra from 2019 to 2023 using a Spatial Lag Fixed Effects Model. The research integrates spatial analysis and panel data approaches to identify determinants of the FSI and assess spatial spillover effects between regions. Secondary data were obtained from the Statistics Agency (BPS) and the National Food Agency. The results reveal significant spatial autocorrelation in most years, except 2023. The best-fitting model is the Spatial Lag Fixed Effects Model. Changes in land area, food expenditure, and rice productivity significantly improve FSI, while non-food expenditure and economic growth do not show a positive effect. The findings emphasize the importance of incorporating spatial dependencies in regional food security policies. Moreover, significant spillover effects indicate that improvements in one area can influence neighboring regions. Therefore, inter-regional cooperation and integrated food distribution policies are essential to achieving sustainable food security.